PRIMARY METABOLITE QUALITATIVE TEST OF BINTARO PLANT (CarberaodollamGaertn) AS A PEST BIOPESTICIDE Rattus argentiventer - Risnawati; Susanti, Rini; Fadhillah, Wiznie (Jurnal Online Pertanian Tropik, 2020)
Abstract Bintaro is a plant that contains poison in all parts of the plant. Cardiac glycoside compounds contained in Bintaro plants can be used as biopesticides to repel rats. Rat pests are one of the important pests in rice plants that are difficult to control, so rice production always decreases. Therefore it is necessary to look for an effective, efficient and environmentally friendly control technology, namely by using Bintaro plant extracts which are able to become biopesticides to repel rat pests. The purpose of this study was to determine the primary compound of the Bintaro plant (CarberaodollamGaertn) which acts as a repellent for thepest Ratusargiventer. The method used in this research is qualitative testing using phenol method to test the content of primary metabolites in the leaves and stems of Bintaro plants. From the results of the research conducted, it was found that the qualitative levels of primary metabolites from Bintaro leaves and stems contained protein content. Fat and carbohydrate content.